2005
DOI: 10.4103/0378-6323.18944
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of skin and nerve histopathology in single skin lesion leprosy

Abstract: Single skin lesion without thickened peripheral nerves as criteria for single dose ROM therapy is not logical, since the histological diagnosis of leprosy in normal looking nerves with presence of AFB is revealed in this study. Pure cutaneous nerve biopsy is a simple outpatient procedure, without complications. This study emphasizes the need to consider nerve pathology as an important tool for further therapeutic recommendations, than just clinical trials and skin pathology alone. Though single dose ROM therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…Another study reported epithelioid granulomas in 14% cases. [ 13 ] Reduction in myelinated fibres was noted in 55.6% cases,[ 16 ] unlike moderate-to-complete degree of myelinated fiber loss in all the cases in this study. Loss of myelinated fiber and Schwann cells is consistent with decrease in immunohistochemical staining of neurofilament in 100% HN biopsies, nerve growth factor receptor loss in 81.8%, PGP 9.5 staining loss in 100%, and loss of S-100 as well as myelin basic protein immunoreactivity in 90.9% cases each.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Another study reported epithelioid granulomas in 14% cases. [ 13 ] Reduction in myelinated fibres was noted in 55.6% cases,[ 16 ] unlike moderate-to-complete degree of myelinated fiber loss in all the cases in this study. Loss of myelinated fiber and Schwann cells is consistent with decrease in immunohistochemical staining of neurofilament in 100% HN biopsies, nerve growth factor receptor loss in 81.8%, PGP 9.5 staining loss in 100%, and loss of S-100 as well as myelin basic protein immunoreactivity in 90.9% cases each.…”
Section: Discussionmentioning
confidence: 61%
“…[ 15 ] Reddy et al . described dichotomy between immunological grading of skin and nerve lesions in cases where both are involved simultaneously, with the nerve showing lower spectrum of the disease,[ 16 ] and such a finding was noted only in case-4.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, não foi possível quantificar esta discordância devido à existência de múltiplas HDCs na maioria dos pedidos. O diagnóstico diferencial de Hanseníase inclui muitas doenças, e é comum a não correlação entre a clínica e a histopatologia das lesões suspeitas de Hanseníase 1, 11,16,17,19,20,25,26 . Na avaliação morfológica dos granulomas, especialmente no sentido do pólo tuberculóide, não é possível distinguir a Hanseníase de outras dermatoses granulomatosas, como a Paracoccidioidomicose sarcoídica, a Sífilis secundária tardia e a Sarcoidose 22 .…”
Section: -Resultadosunclassified
“…Considerando ainda outra forma de classificação, baseada apenas na clínica, Rao et al (2006) avaliaram 77 pacientes com formas clinicamente paucibacilares (de uma a cinco lesões) e encontraram 63% de correlação clínico-histopatológica para a forma dimorfa tuberculóide, e quatro casos de forma dimorfa lepromatosa 19 . Em 2005, Reddy et al 26 avaliaram 27 pacientes não tratados, com lesão única e sem comprometimento neural clínico, encontrando correlação clínico-patológica da pele de 51,8%, entre pele e nervo de 26%, e em 55,5% os nervos estavam acometidos. Na análise de biópsias de pele aparentemente normal de 50 pacientes com hanseníase, El-Darouti et al (2006) 27 encontraram alterações características da doença em 52% dos casos.…”
Section: -Resultadosunclassified
“…In a study done by Reddy et al, it was noted that the duration of symptoms ranged from 1 month to 14 months. 7 Clinically, BT was the most common type of leprosy with 28 patients (62.2%) and TT was the least diagnosed type with 1 patient (2.2%). This is similar to the study done by Giridhar et al (BT 44%).…”
Section: Discussionmentioning
confidence: 99%